Root exudation under maize/soybean intercropping system mediates the arbuscular mycorrhizal fungi diversity and improves the plant growth - Zhang, Shu; Li, Shumin; Meng, Lingbo; Liu, Xiaodan; Zhang, Yuhang; Zhao, Shuchang; Zhao, Haobing (Frontiers in Plant Science, 2024)
Maize/soybean intercropping is a common cropping practice in Chinese agriculture, known to boost crop yield and enhance soil fertility. However, the role of below-ground interactions, particularly root exudates, in maintaining intercropping advantages in soybean/maize intercropping systems remains unclear. This study aimed to investigate the differences in root exudates between intercropping and monocropping systems through two pot experiments using metabolomics methods.Multiple omics analyses were conducted to explore correlations between differential metabolites and the community of Arbuscular Mycorrhizal Fungi (AMF), shedding light on the mechanisms underlying the dominance of intercropping from the perspective of root exudates-soil microorganism interactions. The study revealed that intercropping significantly increased the types and contents of root exudates, lowered soil pH, increased the availability of nutrients like available nitrogen (AN) and available phosphorus (AP), and enhanced AMF colonization, resulting in improving the community composition of AMF. Besides, root exudates in intercropping systems differed significantly from those in monocropping, with 41 and 39 differential metabolites identified in the root exudates of soybean/maize, predominantly amino acids and organic acids. The total amount of amino acids in the root exudates of soybean intercropping was 3.61 times higher than in monocropping. Additionally, the addition of root exudates significantly improved the growth of soybean/maize and AMF colonization, with the mycorrhizal colonization rate in intercropping increased by 105.99% and 111.18% compared to monocropping, respectively. The identified metabolic pathways associated with root exudates were closely linked to plant growth, soil fertility improvement, and the formation of AMF. Correlation analysis revealed a significant relationship (P < 0.05) between certain metabolites such as tartaric acid, oxalic acid, malic acid, aspartic acid, alanine, and the AMF community. Notably, the photosynthetic carbon fixation pathway involving aspartic acid showed a strong association with the function of Glomus_f_Glomerace, the dominant genus of AMF. A combined analysis of metabolomics and high throughput sequencing revealed that the root exudates of soybean/maize intercropping have direct or indirect connections with AMF and soil nutrients. This suggests that the increased root exudates of the soybean/maize intercropping system mediate an improvement in AMF community composition, thereby influencing soil fertility and maintaining the advantage of intercropping.